POTENTIAL OF THE RESEARCH ENERGY CENTRE TO ENHANCE ENERGY SPECIALISATIONS IN THE SAVINJA-ŠALEK REGION - Marta Svetina Veder (Journal of Energy Technology, 2024)
This article tackles the significance and potential of the company RCE (Research Energy Centre) to implement a regional development programme and national development goals. RCE was founded in 2011 by the largest energy companies (and companies in other fields) in the Savinja-Šalek subregion in order to establish a unified development centre for energy activities. This was done to accelerate regional economic growth, emphasising the unifying role of RCE to unite the research& development projects of its founders. The priority of RCE is research & development activity based on the exploitation of a wide range of traditional local knowledge, experience and specialisation in the energy sector. Therefore, it enables the creation of quality workplaces and, in the future, it off employment possibilities for promising young experts to be involved in new innovative projects. This is also the way RCE will enhance and enable a prudent regional specialisation, which is one of priority goals of the national development strategies for the year 2020.